(untitled) (Revista Iberoamericana de Bioética, 2025)
The recent ruling by the Ecuadorian Constitutional Court decriminalizing active euthanasia under certain conditions is a momentous milestone in Ecuadorian law, as it sets a precedent by recognizing the right to a dignified death as an extension of the right to a dignified life and the free development of personality. This ruling forces lawyers and physicians to rethink the limits of fundamental rights and patient autonomy in the context of incurable diseases and extreme suffering. In this regard, this paper presents a brief observation on Bioethics and Law, analyzing Constitutional Court Ruling 67-23-IN/24.